Policy Analysis of Teacher Professional Development in Community Schools in Nepal - Tamang, Yam Bahadur (Educational Journal, 2025)
This study intends to analyze the Teacher Professional Development (TPD) policy provision for community schools’ teachers in Nepal. Specifically, this paper examines the policy text, teachers’ understanding, local practices, and how policies affect their professional lives. I adopted the qualitative research design to explore the subjective experiences of teachers. The unstructured interview was administered with three community school teachers. Along with the TPD policy document was analyzed to explore the policy provision on teacher training was analyzed. This study indicates that the teacher professional development framework emphasizes giving the competency-based training package in two phases for teachers. Teachers are perceiving positively to this training program, positively in the development of professional skills, viz., lesson plan preparation, teaching materials construction, and action research preparation. Though it was found that teachers are taking this training program only for their promotion purposes rather than improving the teaching and learning activities in the classroom. This study claims that the TPD policy is conceptually sound, but due to poor implementation, the policy does not seem to have achieved the expected results. However, it seems to have contributed to the professional knowledge, skills development and promotion of teachers in their professional lives.